The book of Job – the real meaning of justice, faith and evilness? A Bible scripture in the Old Testament about man’s relationship to God, faith, evilness and the meaning of justice - Christensen Carsten Sander (Studia Humanitatis, 2019)
The Book of Job and the story of Joseph, Son of Jacob, are both renowned as some of the greatest masterpieces, not only in the Bible, but also in all of the world literature ever. The text was written down in the sphere of ancient Israel’s perception of culture, religion and understanding of life. However, the Book of Job is one of the most mysterious scriptures in the Bible. Together with the two other Wisdom Books of the Old Testament – Proverbs and the Ecclesiastes – it is a unique text of the fundamental meaning of faith and justice in the Holy Book. In this article, the author tries to analyse some of the most profound theological and philosophical questions raised in the book of Job, by telling the story of Job from the land of Uz in the frame of the culture and religion of ancient Israel. Moreover, the question how the Book of Job is relevant for mankind in our days will be asked. The question will be tried answered through an analysis of the Russian movie “Leviathan” by the director Andrey Zvyagintsev.